Papua New Guinea : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2018)
The Papua New Guinea (PNG) economy has grown sluggishly in recent years, reflecting a combination of domestic and external factors. External factors have included adverse terms of trade movements, a drought, and, in 2018, a large earthquake. Domestic factors have included a difficult fiscal consolidation and a shortage of foreign exchange, sustained by an overvalued exchange rate, leading to import compression and weak investment in the non-resource sector. The main macroeconomic challenges for the government are to finish putting in place policies that will help promote economic stability, and to strengthen its long-term development framework. In 2017-18, the new government made important progress in narrowing the fiscal deficit, and adopted a medium-term revenue strategy. But progress on fiscal consolidation has stalled, and the debt-to-GDP ratio is well above the medium-term target. Monetary authorities have begun to facilitate exchange rate adjustment and strengthening of the monetary framework. Stronger economic policies, involving more ambitious fiscal consolidation coupled with faster exchange rate adjustment would yield favorable results.